Visible-light-induced methylsulfonylation/bicyclization of C(sp3)-tethered 1, 7-enynes using a DMSO/H2O system. Issue 10 (4th April 2018) - Huang, Min-Hua; Zhu, Chi-Fan; He, Chun-Lan; Zhu, Yi-Long; Hao, Wen-Juan; Wang, De-Cai; Tu, Shu-Jiang; Jiang, Bo
Abstract : A visible light photocatalytic methylsulfonylation/bicyclization of C(sp 3 )-tethered 1, 7-enynes has been established using a dimethyl sulfoxide (DMSO)/H2 O system as the methylsulfonyl source. Abstract : A visible light photocatalytic methylsulfonylation/bicyclization of C(sp 3 )-tethered 1, 7-enynes has been established using a dimethyl sulfoxide (DMSO)/H2 O system as the methylsulfonyl source. This reaction worked readily to access a wide range of sulfone-containing benzo[ a ]fluoren-5-ones with one quaternary carbon centre and generally good yields through C–S bond cleavage of DMSO. The reaction mechanism was proposed based on the control experiments.